Managing Apple devices : deploying and maintaining iOS 7 and OS X Mavericks devices - Dreyer, Arek (Peachpit Press, 2015)
Managing Apple Devices covers a wide range of technologies that help you manage both iOS and OS X devices. This guide will teach you to formulate an effective plan for deploying and maintaining groups of Apple devices using iOS 7 and OS X Mavericks. You will be introduced to a variety of Apple management technologies including Mobile Device Management, the Volume Purchase Program, and the Device Enrollment Program. You will learn the theory behind these tools and may work through practical exercises that teach you to use the tools. For example, not only will you learn how to use Profile Manager-Apple's implementation of Mobile Device Management-but you will also learn about the ideas behind profile management, how to make configuration easier for both administrators and users while maintaining a highly secure environment. The exercises contained within this guide are designed to let you explore and learn the tools provided by Apple for deploying and managing iOS and OS X systems. These exercises move along in a somewhat linear fashion, starting with verification of access to necessary services, moving on to the configuration of those services, and finally testing the results of those services on client devices. Each subsequent lesson and exercises can be seen as building on previous topics, with more advanced topics towards the end of the guide. Each lesson in this guide is designed to give technical coordinators and system administrators the skills, tools, and knowledge to deploy and maintain Apple devices by: • Providing knowledge of how Apple deployment technologies work • Showing how to use specific deployment tools • Explaining deployment procedures and best practices • Offering practical exercises step-by-step solutions available Recommendations: The world needs a book like this. The authors convey not only the nuts-and-bolts of how Apple's tools work but also the philosophy behind the tools. This is essential reading for anyone coming to the Apple world from other platforms. We do things differently over here and understanding the philosophy is every bit as important - perhaps more so - than knowing which buttons to press. I commend this book to anyone starting or modernising an Apple deployment. Fraser Speirs Head of Computing and IT Cedars School of Excellence, Greenock, Scotland.